Pengaruh Gross Profit Margin (GPM) dan Inventory Turnover Ratio (ITR) terhadap Pertumbuhan Laba pada PT Gudang Garam Tbk Periode 2014-2024 - Wafiq Soliki; Habibah Habibah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study aims to analyze the influence of Gross Profit Margin (GPM) and Inventory Turnover Ratio (ITR) on profit growth at PT Gudang Garam Tbk during the period 2014–2024. The research employs a quantitative method with a descriptive approach and utilizes multiple linear regression analysis. Data were gathered from financial report documentation and a literature study. The F-test results indicate that GPM and ITR, when considered together, have no significant effect on profit growth, with an F-statistic value of 1.065, which is lower than the F-table value of 5.318, and a significance value of 0.389 > 0.05. Furthermore, the t-test results reveal that GPM (t-statistic 1.122; p = 0.295) and ITR (t-statistic 0.160; p = 0.877) do not have a significant partial effect on profit growth, as the significance values of both variables are higher than 0.05. The findings suggest that GPM and ITR are not the primary factors influencing the company's profit growth. Therefore, it is recommended that external factors such as market conditions, industry trends, and economic variables should be considered more carefully in managerial decision-making. This study contributes to the understanding of financial performance analysis, providing insights for both academics and practitioners in the field of corporate finance.